Comparative Effectiveness of Integrative Care and Conventional Care in Cardiovascular Disease Risk Reduction Among Newly Diagnosed Type 2 Diabetes Mellitus Patients: A Systematic Review of Real-World Data - Khan, Asfandiyar; Petros , Biruktawit; Ali, Shahbaz; Mustafa, Roohana; Khan, Erum; Batool, Aeliya (Indus Journal of Bioscience Research, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) significantly increases the risk of cardiovascular disease (CVD). Integrative care (IC) offers a personalized and multifaceted approach to managing T2DM, but its effectiveness compared to conventional care (CC) in reducing CVD risk remains underexplored. Objective: This systematic review aims to assess the comparative effectiveness of IC versus CC in reducing CVD risk among newly diagnosed T2DM patients, utilizing real-world data. Methods: We conducted a systematic review of studies published from 2014 to 2024 that compared IC and CC in newly diagnosed T2DM patients. Real-world data sources were analyzed, including electronic health records, cohort studies, and registries. Data were extracted on CVD outcomes, glycemic control, lipid profiles, and quality of life. The effectiveness of IC and CC was evaluated using meta-analysis and comparative statistical techniques. Results: The review included 5 studies with a total of 5,450 participants. Integrative care (IC) was associated with a significantly lower risk of major cardiovascular events compared to conventional care (CC), with a hazard ratio (HR) of 0.68 (95% CI: 0.55-0.84). Patients receiving IC demonstrated improvements in glycemic control, lipid profiles, and blood pressure, along with higher quality of life scores. The benefits of IC were especially evident in high-risk populations and among those with extended follow-up periods. Conclusions: Integrative care demonstrates superior effectiveness in reducing CVD risk among newly diagnosed T2DM patients compared to conventional care. The holistic and personalized nature of IC contributes to improved cardiovascular outcomes and overall patient well-being. These findings support the adoption of integrative approaches in diabetes management to enhance long-term health outcomes.